Task-Oriented Circuit Class Training with Motor Imagery versus Motor Imagery for Balance and Gait Rehabilitation in Post-Stroke Patients: An Experimental Study. - Bhutani, Preeti; Senapati, Anurupa (Indian Journal of Occupational Therapy (Wolters Kluwer India Pvt Ltd))
Background: The ability to balance and walk is impaired in around 80% of population after stroke, and there are evidence stating that task-oriented circuit class training (TOCCT) and motor imagery (MI) have a significant impact on balance and gait impairments after stroke. Objective: The study aims to compare the effects of TOCCT with MI versus MI. Study Design: Experimental study. Methods: Thirty stroke patients, both males and females, between ages 30 and 60 years, were divided into two groups after being screened based on inclusion and exclusion criteria. The first group received 15 min of MI training followed by 25 min of TOCCT. The second group received 15 min of MI and 25 min of standard balance and gait training. For both groups, the intervention lasted a total of 40 min, 5 days per week, for 4 weeks. The Rivermead Visual Gait Assessment (RVGA) and the Berg Balance Scale (BBS) were used as outcome measures. Results: The patient's scores were analyzed for both TOCCT with MI group and MI group. Both groups demonstrated significant improvement, as indicated by the Wilcoxon signed-rank test; in TOCCT with MI group, the berg balance score showed a test value −3.449 with a P < 0.001 for 95% CI −6.761, −5.638 and RVGAs also showed a test value −3.449 and P < 0.001 for 95% CI −3.46, 2.53, whereas in the MI group, berg balance score showed a test value −3.475 with a P < 0.001 for 95% CI −3.46, 2.531 and RVGAs also showed a test value −3.472 and P < 0.001 for 95% CI 2.12, 2.94. However, the TOCCT with MI group showed more substantial improvement in berg balance scores (test value −4.651, P < 0.01 with 95% CI 2.501–3.898) and RVGA scores (test value −4.673, P < 0.001 with 95% CI 2.32, 3.81. Conclusion: The TOCCT, when included in occupational therapy sessions along with MI, is beneficial and offers better outcomes for improvement of balance and gait in poststroke patients.